Transition Metal Complexes of Pyridyl Ligand as Light Emitting Materials in OLEDs - Basavaraja, Thippeswamy; Bhadrachar, Somashekara; Mahadevan, Kittappa M.; Vijayakumar, Giriyapura R. (Asian Journal of Chemistry, 2019)
Transition metal complexes, viz., tetrapyridylbis(isothiocyanato)nickel(II) (1), dipyridylbis(isothiocyanato)copper(II) (2) and dipyridylbis-(isothiocyanato)zinc(II) (3) were synthesized by conventional methods. All the synthesized metal complexes were characterized by spectral and elemental analysis. Diffused reflectance (DR) spectra of the complexes 1-3 recorded in the range 200-1100 nm exhibit major peaks at 450 nm and 750 nm (% diffused reflectance 50 and 55, respectively) for complex 1, 500 nm (20 % diffused reflectance) for complex 2 and 400 nm (50 % diffused reflectance) for complex 3. The excitation and emission peaks obtained from photoluminescence spectra indicated the emission of white, green and white lights by the complexes 1, 2 and 3, respectively. From diffused reflectance spectra, the measured band gap energies were found to be 3.95 eV for complex 1, 2.77 eV for complex 2 and 4.3 eV for complex 3. Commission Internationale de l'Eclairage (CIE) coordinates of (0.31533, 0.33082), (0.22605, 0.35099) and (0.28633, 0.31012) were calculated for the complexes 1, 2 and 3, respectively. The phosphors 1-3 were readily soluble in various common organic solvents and they could become promising light emitting materials in organic light emitting diodes (OLEDs).